Orígenes del 'New Urbanism' y su influencia en los paradigmas de desarrollo urbano contemporáneos. - Chávez Martínez, Sander Said; Badillo Jimenez, Walberto Lucas (Revista: Módulo Arquitectura CUC, 2017)
There exist cities which have inherited issues from the industrialized modernism, these have been analyzed by processes of reinvention by using a post-modernist sustainability-based theoretical approach that justifies specific requirements to create a new urban paradigm, in accordance with the interests of citizens in the late twentieth century. With regard to the premises of the mentioned design movement these have enhanced environmentally friendly habits throughout the world, conversely Ibero-American areas does not have a complete performance of adaptation according with its local conditions, instead of this American standards of construction, conceived in different economic conditions, have been employed; hence it is relevant to point out views form New Urbanism have influenced the architectural proposals in the Caribbean Region of Colombia by using not only conceptual features but also building procedures addressed to the estate market.